Management history : its global past and present - Bowden, Bradley; Lamond, David (Emerald Publishing Limited : Information Age Publishing Inc., 2015)
This book has two broad purposes. First, it seeks to determine whether or not there is a "universal" management model through an examination of circumstance in a number of different nations and industries. Second, it brings to a wider audience some of the leading research in the field of management history. In doing so, it highlights the importance of the Management History Division of the Academy of Management in fostering and disseminating new understandings of management and its development. The book indicates that, while there has been much variance in managerial practices across time and space, we can nevertheless speak of a "universal" managerial model.Emerging in association with Britain's Industrial Revolution, the spread of competitive pressures progressively demanded that enterprises respond in broadly common ways if they were to survive. These broad commonalities can be seen in the diverse industries that this book considers - the beef industry of the Northern Plains of the United States in the nineteenth century, the trading activities of the Dutch East India Company, the United States and Australian railroads, and the manufacturing methods of the Ford Motor Company during the early twentieth century. In each of these circumstances, industries and firms had to constantly adapt to changes in both capital and consumer markets. This is evident even in the case of the Ford Motor Company which, as James Wilson's chapter indicates, was in its early days "flexible" rather than Fordist, constantly adjusting production and inventories in accordance with consumer demand. Such responses to global markets is also found in the realms of ideas and education, where the book's study of trends in business education highlights the growing dominance of commercial factors and of intellectual concepts stemming from the United States.The power of management commonalities is also found in the book's study of Australia and the United States. In Australia, governments long sought to isolate the national economy from global trends so as to boost manufacturing and local employment. Ultimately, however, this proved unsuccessful as Australian production became increasingly uncompetitive. A severe process of economic readjustment, with often adverse social effects, is also found in the book's chapter on the United States, which highlights the major changes that have occurred since the 1960s. This book also considers how managerial organizations have been forced to adapt and the intellectual debates that have accompanied this. Finally, in Regina Greenwood's chapter, we have an account of the Management History Division of the Academy of Management, an organization which has provided the fulcrum for the generation and dissemination of management history for the last 3 decades.
Keywords: Management -- History.; Business & Economics -- Management.; Management and management techniques.; elektronické knihy; electronic books